2009
DOI: 10.4049/jimmunol.0901466
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does the Route of Immunization Play in the Generation of Protective Immunity against Mucosal Pathogens?

Abstract: The route of vaccination is important in influencing immune responses at the initial site of pathogen invasion where protection is most effective. Immune responses required for mucosal protection can differ vastly depending on the individual pathogen. For some mucosal pathogens, including acute self-limiting infections, high-titer neutralizing Abs that enter tissue parenchyma or transude into the mucosal lumen are sufficient for clearing cell-free virus. However, for pathogens causing chronic infections such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
178
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(186 citation statements)
references
References 90 publications
8
178
0
Order By: Relevance
“…The major point of entry for many pathogens is the gastrointestinal or respiratory tract, or the genital mucosa (reviewed in Ref. 45), suggesting that mucosal protective immune responses must be induced to counteract pathogen dissemination. However, the ways by which mucosal immunization could generate protective frontline immunity against pathogens remain largely undefined.…”
Section: Discussionmentioning
confidence: 99%
“…The major point of entry for many pathogens is the gastrointestinal or respiratory tract, or the genital mucosa (reviewed in Ref. 45), suggesting that mucosal protective immune responses must be induced to counteract pathogen dissemination. However, the ways by which mucosal immunization could generate protective frontline immunity against pathogens remain largely undefined.…”
Section: Discussionmentioning
confidence: 99%
“…As mucosal surfaces represent the major entry fro many human pathogens (including HSV, HIV, respiratory viruses, as well as mycobacteria), induction of mucosal [18,19] .…”
Section: Role Of Virus-specific Cellular Immune Response In Transplanmentioning
confidence: 99%
“…Massive depletion of CD4 1 CCR5 1 memory T cells occurs in the mucosal tissues within the first 2 weeks of HIV-1 infection [1,2]. In connection with this, vaccines providing protection against gastrointestinal infectious diseases must be able to induce long-term mucosal immune responses [3][4][5][6][7][8][9]. Previously, we demonstrated that long-lasting protection against mucosal viral transmission could be accomplished by CD8 1 CTLs that must be present at the mucosal site of antigen exposure, although some mucosal memory CTLs may be induced even after systemic vaccination [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%